TINJAUAN YURIDIS TERHADAP EFISIENSI PERUSAHAAN SEBAGAI ALASAN PEMUTUSAN HUBUNGAN KERJA - Abdul Rasyid Lukman Siregar; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Companies in carrying out their operational activities often deal with economicproblems and market conditions that cause companies to suffer losses so that it is necessaryto take efficiency measures to maintain the continuity of the company's operations. One formof efficiency that is often done by employers is to reduce the number of workers byterminating employment.This research is a Normative legal research, which is a library research thatexplains the principles of law such as applicable laws and regulations and is associated withlegal theories related to the problem under study. This research was conducted to find outhow the concept of termination of employment is regulated in Article 164 Paragraph (3) ofLaw Number 13 of 2003 concerning Employment on the Decision of the Constitutional CourtNumber 11 / PUU-IX / 2011, how to review cases of termination of employment for reasonsof company efficiency, and how legal protection and justice in termination of employment aredue to reasons of company efficiency.The conclusion of this research is, First, the word "efficiency" contained in Article164 Paragraph (3) of Law Number 13 Year 2003 Juncto Decision of the Constitutional CourtNumber 19 / PUU-IX / 2011 cannot be interpreted as a reason for termination ofemployment, however It must be interpreted that termination of employment can be carriedout by the company if the company closes and the closing of the company is as a form ofefficiency, or in other words the entrepreneur performs efficiency by closing the company.Second, the use of Article 164 Paragraph (3) of Law Number 13 Year 2003 as a legal basisfor Termination of Employment for reasons of efficiency without the closure of companybusiness is inappropriate and not of legal certainty. Third, the absence of a provision thatexplicitly prohibits termination of employment due to efficiency reasons in order to maintainthe continuity of company operations results in the absence of certainty that can providelegal protection for workers and employers. Fourth, termination of employment for reasonsof efficiency which aims to maintain the continuity of the company's operations so that it doesnot close is unavoidable and must be seen as a solution that provides benefits for a number ofother employees so that they can continue to work. Efficiency which is used as a reason fortermination of employment will be fair if there is compensation from employers to workersthat are reasonable and balanced. The writer's suggestion on the problem under study is, thegovernment must revise the Manpower Act or make new legislation regarding termination ofemployment in the context of efficiency aimed at maintaining the continuity of the company'soperations.Keywords: Termination of Employment - Efficiency - Employers - Companies - Workers